1999
DOI: 10.1007/s004649900886
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thoracoscopy in trauma

Abstract: Analysis suggests that thoracoscopy (nonvideo and VATS) can be applied safely and effectively in the care of the injured patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 29 publications
5
89
0
18
Order By: Relevance
“…In a review by Villavicencio and Aucar, in two prospective studies screening laparoscopy for blunt trauma reported sensitivity of 90 to 100%, specificity of 86 to 100%, and accuracy of 88 to 100%. 2 In nine prospective series, screening laparoscopy for penetrating trauma reported sensitivity of 85 to 100%, specificity of 73 to 100% and accuracy of 80 to 100% with 2 procedure-related complications among 543 patients. 2 Diagnostic laparoscopy for blunt trauma reported sensitivity of 100%, specificity of 91%, and accuracy of 96%; for penetrating trauma, sensitivity of 80 to 100%, specificity of 38 to 86%, and accuracy of 54 to 89%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review by Villavicencio and Aucar, in two prospective studies screening laparoscopy for blunt trauma reported sensitivity of 90 to 100%, specificity of 86 to 100%, and accuracy of 88 to 100%. 2 In nine prospective series, screening laparoscopy for penetrating trauma reported sensitivity of 85 to 100%, specificity of 73 to 100% and accuracy of 80 to 100% with 2 procedure-related complications among 543 patients. 2 Diagnostic laparoscopy for blunt trauma reported sensitivity of 100%, specificity of 91%, and accuracy of 96%; for penetrating trauma, sensitivity of 80 to 100%, specificity of 38 to 86%, and accuracy of 54 to 89%.…”
Section: Discussionmentioning
confidence: 99%
“…2 In nine prospective series, screening laparoscopy for penetrating trauma reported sensitivity of 85 to 100%, specificity of 73 to 100% and accuracy of 80 to 100% with 2 procedure-related complications among 543 patients. 2 Diagnostic laparoscopy for blunt trauma reported sensitivity of 100%, specificity of 91%, and accuracy of 96%; for penetrating trauma, sensitivity of 80 to 100%, specificity of 38 to 86%, and accuracy of 54 to 89%. 2 Missed injuries with screening laparoscopy were 0.4% (6 of 1708 patients) and laparoscopyrelated complications were 1.3% (22 of 1672 patients).…”
Section: Discussionmentioning
confidence: 99%
“…По мнению многих авторов, применение видео эндоскопической техники представляется весьма перспективным при решении данных такти-ческих вопросов, обеспечивает проведение полно-ценной ревизии и, во многих случаях, адекватно-го устранения повреждений [8,10,11,33,[37][38][39][40]. В многочисленных сообщениях последних лет сре-ди главных преимуществ применения торакоскопии при травме называются: малая травматичность, со-поставимая с дренированием плевральной полости; уменьшение частоты диагностических торакото-мий; снижение интенсивности болевого синдрома в послеоперационном периоде; сокращение сроков госпитализации и реабилитации пациентов [6,26,[41][42][43][44]. Так, Н.А.…”
Section: актуальностьunclassified
“…По данным известной аналитической работы Villavicencio и соавт. [43], диагностическая точность торакоскопии при повреждениях диафрагмы соста-вила 98%. В уже упомянутом нами обзоре Г.М.…”
Section: диагностические возможностиunclassified
See 1 more Smart Citation